Lithium-rich manganese-based precursor material as well as preparation method and application thereof

By preparing lithium-rich manganese-based precursor materials with mixed sheet and spherical morphologies, the problems of poor material compaction density and energy density in the prior art were solved, and battery performance with high energy density and long cycle life was achieved.

CN120887459AActive Publication Date: 2025-11-04GANZHOU NUOWEI NEW ENERGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202511105194.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-07
Publication Date
2025-11-04
Estimated Expiration
2045-08-07

AI Technical Summary

Technical Problem

Existing processes for preparing lithium-rich manganese-based cathode materials tend to result in poor compaction density and energy density, and these processes also make it difficult to achieve close packing of particles and uniform reaction.

Method used

A method for preparing lithium-rich manganese-based precursor materials is adopted. Solution A is formed by mixing manganese salt and N metal salt, and a co-precipitation reaction is carried out under a protective atmosphere. By controlling the solution concentration and reaction conditions, a precursor material with mixed morphologies of sheet-like and quasi-spherical shapes is prepared. Subsequently, it is mixed with lithium salt and calcined to form lithium-rich manganese-based cathode material.

Benefits of technology

It improves the compaction density and volumetric energy density of the material, enhances electrochemical performance and cycle stability, reduces the probability of side reactions, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120887459A_ABST
    Figure CN120887459A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of battery materials, and discloses a lithium-rich manganese-based precursor material as well as a preparation method and application thereof. The molecular formula of the lithium-rich manganese-based precursor material is Mn1-m-nNn (OH) 2, N is one or more than two of Ni, Co, Fe, Al and Zn, the value range of m is more than or equal to 0.1 and less than or equal to 0.4, and the value range of n is more than or equal to 0 and less than or equal to 0.4; the morphology of the lithium-rich manganese-based precursor material is a mixed morphology of sheet-shaped particles and sphere-like particles, the sheet-shaped particles are polygonal, and the sphere-like particles are distributed among the sheet-shaped particles. The positive electrode material obtained after lithiation of the lithium-rich manganese-based precursor material at high temperature is good in compaction density and tap density, and the electrochemical performance of the battery can be improved when the positive electrode material is applied to the battery.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of battery materials, and relates to a lithium-rich manganese-based positive electrode material, in particular to a lithium-rich manganese-based precursor material and a preparation method and application thereof. BACKGROUND

[0002] Compared with LiCoO2, metal oxide positive electrode materials are widely used due to relatively low price, good thermal stability and good cycle performance. The lithium-rich phase xLiMO2·(1-x)Li2MnO3 in the lithium-rich xLiMO2·(1-x)Li2MnO3 material can be regarded as a continuous solid solution formed by Li2MnO3 and LiMO2 (M represents a transition metal).

[0003] The structure of the lithium-rich material is relatively complex. In the charging and discharging process, the migration of lithium ions and the charge compensation mechanism not only involve the structural change of the bulk lattice, but also are accompanied by the interface reaction between the surface and the electrolyte, and the lattice oxygen (not only the transition metal ion) participates in the redox reaction, resulting in a complex reaction process and multiple regions synchronously proceeding.

[0004] In the prior art, the commonly used preparation processes for preparing the lithium-rich manganese-based positive electrode material include a solid phase method and a liquid phase method. The solid phase method usually involves mechanically mixing raw materials and then high-temperature calcining. During calcining, particles of uneven sizes (from sub-micron to micron mixed) are easily formed, and high temperature easily leads to particle agglomeration, which destroys the sphericity and dispersibility of the particles, the particle morphology is irregular, the particle size distribution is wide, the packing time interval is large, it is difficult to reduce the porosity by compaction, and the compaction density is low.

[0005] Although the liquid phase method can improve the uniformity of components, some process details may still cause compaction performance defects. The liquid phase method includes a coprecipitation method and a sol-gel method. The coprecipitation method easily generates precursor particles with too small particle sizes, which are easily agglomerated into loose secondary particles after calcining, or the particle size distribution is too wide, and the proportion of small particles filling the gap between large particles is unbalanced, resulting in a decrease in packing efficiency. The sol-gel method forms a powder by calcining after gel drying, but if the gel network is uneven, cracks or porous structures will be generated due to different local shrinkage rates during calcining, which increases the internal porosity of the particles, and the particles are easily broken during the compaction process due to the internal porosity, and cannot form a tight packing.

[0006] In general, the existing preparation processes for the lithium-rich material all easily lead to poor compaction density and energy density of the material. SUMMARY

[0007] In view of the defects and deficiencies of the prior art, in a first aspect, the present application provides a lithium-rich manganese-based precursor material; in a second aspect, the present application provides a preparation method of the lithium-rich manganese-based precursor material; in a third aspect, the present application provides a lithium-rich manganese-based positive electrode material; in a fourth aspect, the present application provides a preparation method of the lithium-rich manganese-based positive electrode material; and in a fifth aspect, the present application provides a battery.

[0008] In a first aspect, the present application provides a lithium-rich manganese-based precursor material, the lithium-rich manganese-based precursor material has a molecular formula of Mn 1-m-n N n (OH)2, wherein N is one or two or more of Ni, Co, Fe, Al, and Zn, m has a value range of 0.1≤m≤0.4, and n has a value range of 0≤n≤0.4; the lithium-rich manganese-based precursor material has a mixed morphology of flaky particles and spherical-like particles, the flaky particles are polygonal, and the spherical-like particles are distributed between the flaky particles.

[0009] Preferably, the D50 of the spherical-like particles is 100-500 nm.

[0010] In a second aspect, the present application provides a preparation method of the lithium-rich manganese-based precursor material, comprising the following steps: Step 1, mixing manganese salt, N metal salt, and water to form a solution A; Step 2, first-stage co-precipitation: introducing the solution A, ammonia water, an additive, and a sodium hydroxide solution into a reaction system respectively, and reacting under a protective atmosphere; Step 3, second-stage co-precipitation: adjusting the concentration of the solution A, the concentration of the sodium hydroxide solution, and the rotation speed of the reaction, and continuously introducing the solution A, ammonia water, sodium hydroxide, and the additive into the reaction system to react; Step 4, filtering and drying to obtain the solid particles, which are the lithium-rich manganese-based precursor material.

[0011] Preferably, the manganese salt is any one or two of manganese nitrate and manganese sulfate.

[0012] Preferably, the N element in the N metal salt is any one or two or more of Ni, Co, Fe, Al, and Zn; and the N metal salt is a nitrate or a sulfate.

[0013] Preferably, the additive is any one or two or more of a PVP (polyvinylpyrrolidone) solution, a CTAB (cetyltrimethylammonium bromide) solution, and a SDS (sodium dodecyl sulfate) solution.

[0014] Preferably, in step 1, the molar amount of the manganese salt and the N metal salt is the same as the ratio of Mn and N in the molecular formula of the lithium-rich manganese-based precursor material.

[0015] Preferably, in step 2, the concentration of solution A is 30-50 g / L; the concentration of sodium hydroxide is 40-60 g / L; the concentration of ammonia is 15-40 wt%; the concentration of the additive is 50-100 g / L; the flow rate of solution A is 30-100 L / h; the flow rate of sodium hydroxide solution is 30-100 L / h; the flow rate of ammonia is 10-18 L / h; and the flow rate of the additive is 10-18 L / h.

[0016] Preferably, in step 2, the rotation speed of the reaction is 100-200 rpm / min, the reaction time is 2-5 h, and the reaction temperature is 35-55℃.

[0017] Preferably, in step 3, the concentration of solution A is 70-100 g / L; the concentration of sodium hydroxide is 70-100 g / L; the concentration of ammonia is 15-40 wt%; the concentration of the additive is 50-100 g / L; the flow rate of solution A is 30-100 L / h; the flow rate of sodium hydroxide solution is 30-100 L / h; the flow rate of ammonia is 20-50 L / h; and the flow rate of the additive is 20-40 L / h.

[0018] Preferably, in step 3, the rotation speed of the reaction is 220-260 rpm / min, the reaction time is 0.5-2 h, and the reaction temperature is 35-55℃.

[0019] In a third aspect, the present application provides a lithium-rich manganese-based positive electrode material, which has a molecular formula of Li 1+m Mn 1-m-n N n O2, wherein N is one or two or more of Ni, Co, Fe, Al, and Zn, m is in a range of 0.1≤m≤0.4, and n is in a range of 0≤n≤0.4; the lithium-rich manganese-based positive electrode material has a mixed morphology of sheet-like particles and spherical-like particles; the sheet-like particles are polygonal; and the spherical-like particles are distributed between the sheet-like particles.

[0020] Preferably, the D50 of the spherical-like particles is 100-500 nm.

[0021] Preferably, the tap density of the lithium-rich manganese-based positive electrode material is 3.0-3.8 g / cm 3 ; and the tap density of the lithium-rich manganese-based positive electrode material is 1.5-2 g / cm 3 .

[0022] In a fourth aspect, the present application provides a preparation method of a lithium-rich manganese-based positive electrode material, which comprises the following steps: mixing a lithium-rich manganese-based precursor material obtained by the above-mentioned preparation method or the above-mentioned precursor with lithium, and then calcining the mixture in an oxygen-containing atmosphere.

[0023] Preferably, the lithium salt is any one or two or more of lithium carbonate, lithium nitrate, and lithium acetate.

[0024] Preferably, the molar ratio of lithium in the lithium-rich manganese-based precursor material and the lithium salt is 1:1.24~1.9.

[0025] Preferably, the calcination temperature is 900~1100℃, and the calcination time is 10~30h.

[0026] In the fifth aspect, the application provides a battery comprising the lithium-rich manganese-based positive electrode material or the lithium-rich manganese-based positive electrode material prepared by the preparation method.

[0027] Compared with the prior art, the application has the following obvious beneficial effects: (1) The application provides a lithium-rich manganese-based precursor material with special morphology, wherein the sheet-like material is beneficial to improve the reaction kinetics of the material, and after the sheet-like gap is filled with spherical particles, the volume energy density of the material can be effectively improved. The positive electrode material obtained by lithiumizing the lithium-rich manganese-based precursor material at high temperature has good tap density and vibration density, and the application of the positive electrode material in the battery can improve the electrochemical performance of the battery.

[0028] (2) The process for preparing the lithium-rich manganese-based precursor material provided by the application is simple, does not need to adjust the existing production line, and is beneficial to industrialization. BRIEF DESCRIPTION OF DRAWINGS

[0029] Figure 1 SEM image of the lithium-rich manganese-based positive electrode material prepared in Example 1 under 6000 times magnification; Figure 2 SEM image of the lithium-rich manganese-based positive electrode material prepared in Example 1 under 5000 times magnification; Figure 3 SEM image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 1; Figure 4 SEM image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 2; Figure 5 Cycle curve schematic diagram of the battery assembled by the positive electrode materials prepared in Examples 1~3 and Comparative Examples 1~2. DETAILED DESCRIPTION

[0030] The application provides the following specific technical solutions.

[0031] In the first aspect, the molecular formula of the lithium-rich manganese-based precursor material is Mn 1-m-n N n(OH)2, wherein N is one or more of Ni, Co, Fe, Al, and Zn, m ranges from 0.1 to 0.4, and n ranges from 0 to 0.4; the lithium-rich manganese-based precursor material has a mixed morphology of sheet-like and spherical shapes, the sheet-like particles are polygonal, and the spherical particles are distributed among the sheet-like particles.

[0032] Through research, the inventors discovered that sheet-like particles have a large two-dimensional plane, while spherical particles have a three-dimensional symmetrical structure. When the two are mixed, the spherical particles can fill the gaps between the sheet-like particles, reducing voids and gaps between particles and significantly improving the packing density of the precursor. This high packing density helps reduce the volume voids in the cathode material during subsequent sintering with the lithium source, ultimately increasing the energy density of the electrode.

[0033] The planar structure of plate-like particles provides more lithium-ion diffusion channels and shortens the ion migration path; while spherical particles have a higher specific surface area, which increases the contact area with the electrolyte and promotes ion transport. The particle structure formed by the mutual support of the two morphologies can reduce electron conduction resistance, reduce polarization, and improve the cycling stability of the material.

[0034] Spherical particles distributed between the plate-like particles act as a buffer and support, alleviating stress concentration caused by lattice expansion / contraction during charging and discharging, and reducing particle breakage or pulverization. The hierarchical porous structure formed by the mixed morphology (micropores between the plate-like gaps and spherical particles) enhances the electrolyte's permeability, making the surface of the active material easier to wet with the electrolyte and preventing capacity decay caused by excessive local reactions. The synergistic effect between particles promotes uniform lithium-ion insertion / extraction throughout the electrode, reduces local concentration gradients, lowers the probability of side reactions (such as electrolyte decomposition), and extends battery cycle life.

[0035] In summary, the hybrid morphology, through structural complementarity, balances packing density, transport kinetics, mechanical stability, and reaction uniformity, laying the foundation for high energy density, high rate performance, and long cycle life of lithium-rich manganese-based cathode materials.

[0036] Preferably, the D50 of the spherical particles is 100~500nm.

[0037] Secondly, the present invention provides a method for preparing a lithium-rich manganese-based precursor material, comprising the following steps: Step 1: Mix manganese salt, nitrogen metal salt and water to form solution A; Step 2, First stage coprecipitation: Solution A, ammonia, additive, and sodium hydroxide solution are introduced into the reaction system respectively, and the reaction is carried out under a protective atmosphere; Step 3, second stage co-precipitation: adjust the concentration of solution A, the concentration of sodium hydroxide solution, the rotation speed of the reaction, continue to introduce solution A, ammonia, sodium hydroxide, additives into the reaction system, and continue the reaction. Step 4, filtration, drying, and the obtained solid particles are the lithium-rich manganese-based precursor material.

[0038] The inventors have found that by adjusting the solution concentration, reaction rotation speed, reaction temperature and other reaction factors, a lithium-rich manganese-based positive electrode material with a mixed morphology of sheet and spherical shape can be prepared by one-step co-precipitation combined with lithiation sintering.

[0039] Preferably, the manganese salt is any one or both of manganese nitrate and manganese sulfate.

[0040] Preferably, the N element in the N metal salt is any one or more than two of Ni, Co, Fe, Al, and Zn; and the N metal salt is a nitrate or a sulfate.

[0041] Preferably, the additive is any one or more than two of PVP (polyvinylpyrrolidone) solution, CTAB (cetyltrimethylammonium bromide) solution, and SDS (sodium dodecyl sulfate) solution.

[0042] The additive can control the growth direction by adsorbing on the surface of the particles. The first stage can inhibit the excessive stacking of sheet particles, and the second stage can stabilize the surface energy of the spherical particles and promote their uniform dispersion.

[0043] Preferably, in step 1, the molar ratio of the manganese salt and the N metal salt to the ratio of Mn and N in the molecular formula of the lithium-rich manganese-based precursor material is the same.

[0044] Preferably, in step 2, the concentration of solution A is 30-50 g / L; the concentration of sodium hydroxide is 40-60 g / L; the concentration of ammonia is 15-40 wt%; the concentration of the additive is 50-100 g / L; the flow rate of solution A is 30-100 L / h; the flow rate of sodium hydroxide solution is 30-100 L / h; the flow rate of ammonia is 10-18 L / h; and the flow rate of the additive is 10-18 L / h.

[0045] Preferably, in step 2, the reaction rotation speed is 100-200 rpm / min, the reaction time is 2-5 h, and the reaction temperature is 35-55℃.

[0046] Preferably, in step 3, the concentration of solution A is 70-100 g / L; the concentration of sodium hydroxide is 70-100 g / L; the concentration of ammonia water is 15-40 wt%; the concentration of the additive is 50-100 g / L; the flow rate of solution A is 30-100 L / h, the flow rate of sodium hydroxide solution is 30-100 L / h; the flow rate of ammonia water is 20-50 L / h, and the flow rate of the additive is 20-40 L / h.

[0047] Preferably, in step 3, the rotation speed of the reaction is 220-260 rpm / min, the reaction time is 0.5-2 h, and the reaction temperature is 35-55℃.

[0048] In a third aspect, the present application provides a lithium-rich manganese-based positive electrode material, which has a molecular formula of Li 1+m Mn 1-m-n N n O2, wherein N is one or two or more of Ni, Co, Fe, Al, and Zn, m is in a range of 0.1≤m≤0.4, and n is in a range of 0≤n≤0.4; the lithium-rich manganese-based positive electrode material has a mixed morphology of sheet and spherical-like shape, the sheet particles are polygonal, and the spherical-like particles are distributed between the sheet particles.

[0049] Preferably, the D50 of the spherical-like particles is 100-500 nm.

[0050] Preferably, the tap density of the lithium-rich manganese-based positive electrode material is 3.0-3.8 g / cm 3 ; and the tap density of the lithium-rich manganese-based positive electrode material is 1.5-2 g / cm 3 .

[0051] In a fourth aspect, the present application provides a preparation method of a lithium-rich manganese-based positive electrode material, which comprises mixing lithium with a lithium-rich manganese-based precursor material prepared by the above method or the above preparation method, and then calcining the mixture in an oxygen-containing atmosphere.

[0052] Preferably, the lithium salt is any one or two or more of lithium carbonate, lithium nitrate, and lithium acetate.

[0053] Preferably, the molar ratio of lithium in the lithium-rich manganese-based precursor material to lithium in the lithium salt is 1:1.24-1.9.

[0054] Preferably, the calcination temperature is 900-1100℃, and the calcination time is 10-30 h.

[0055] In a fifth aspect, the present application provides a battery comprising the lithium-rich manganese-based positive electrode material prepared by the above method or the above preparation method.

[0056] In order to make the technical problems, technical solutions and technical advantages to be solved by the present application more clear, specific examples will be described in detail below, but the protection scope of the present application is not limited to the following specific examples.

[0057] Unless otherwise defined, all the professional terms used below have the same meaning as commonly understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific examples and are not intended to limit the protection scope of the present application.

[0058] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present application can be purchased from the market or can be prepared by existing methods.

[0059] Example 1: A preparation method of a lithium-rich manganese-based positive electrode material, comprising the following steps: Step 1, MnSO4·H2O and CoSO4·6H2O with a molar ratio of 2:1 are dissolved in deionized water to prepare solution A with a concentration of 40 g / L and solution B with a concentration of 80 g / L.

[0060] Step 2, solution A, 35wt% ammonia water, 60g / L SDS solution and 50g / L sodium hydroxide solution are respectively introduced into a continuous stirred tank reactor, the flow rate of solution A and sodium hydroxide is 40L / h, the flow rate of ammonia water and SDS solution is 15L / h, the reaction speed is 140rpm / min, and the reaction is carried out at 40℃ for 4h under the protection of nitrogen atmosphere.

[0061] Step 3, stop introducing solution A and 50g / L sodium hydroxide solution, adjust to introduce solution B and 100g / L sodium hydroxide solution, the flow rate of solution B and sodium hydroxide is 40L / h, ammonia water and SDS solution are continuously introduced, the flow rate of ammonia water and SDS solution is 30L / h. Adjust the reaction speed to 220rpm / min, filter and dry after reaction at 40℃ for 1h to obtain solid particles, which are Mn 0.67 Co 0.33 (OH)2 precursor.

[0062] Step 4, 0.1mol of Mn 0.67 Co 0.33 (OH)2 is mechanically mixed with 0.124mol of lithium hydroxide, and then placed in a muffle furnace for high-temperature sintering at 980℃ for 20h to finally obtain Li 1.1 Mn 0.6 Co 0.3 O2.

[0063] Comparative Example 1: A preparation method of a lithium-rich manganese-based positive electrode material, comprising the following steps: Step 1, MnSO4·H2O and CoSO4·6H2O with a molar ratio of 2:1 are dissolved in deionized water to prepare solution A with a concentration of 40 g / L and solution B with a concentration of 80 g / L.

[0064] Step 2, solution A, 35wt% ammonia, 60g / L SDS solution and 50g / L sodium hydroxide solution are respectively introduced into a continuous stirred tank reactor, the flow rate of solution A and sodium hydroxide is 40L / h, the flow rate of ammonia and SDS solution is 15L / h, the reaction speed is 140rpm / min, after 4h reaction at 40℃ under nitrogen atmosphere protection, filtration and drying are performed, and the obtained solid particles are Mn 0.67 Co 0.33 (OH)2 precursor.

[0065] Step 3, 0.1mol of Mn 0.67 Co 0.33 (OH)2 is mechanically mixed with 0.124mol of lithium hydroxide, and then placed in a muffle furnace for high-temperature sintering at 980℃ for 20h, finally obtaining Li 1.1 Mn 0.6 Co 0.3 O2.

[0066] Comparative example 2: A preparation method of a lithium-rich manganese-based positive electrode material, comprising the following steps: Step 1, MnSO4·H2O and CoSO4·6H2O with a molar ratio of 2:1 are dissolved in deionized water to prepare solution A with a concentration of 40 g / L and solution B with a concentration of 80 g / L.

[0067] Step 2, solution A, 35wt% ammonia, 60g / L SDS solution and 50g / L sodium hydroxide solution are respectively introduced into a continuous stirred tank reactor, the flow rate of solution A and sodium hydroxide is 40L / h, the flow rate of ammonia and SDS solution is 30L / h, the reaction speed is 20rpm / min, after 1h reaction at 40℃ under nitrogen atmosphere protection, filtration and drying are performed, and the obtained solid particles are Mn 0.67 Co 0.33 (OH)2 precursor.

[0068] Step 3, 0.1mol of Mn 0.67 Co 0.33 (OH)2 is mechanically mixed with 0.062mol of lithium carbonate, and then placed in a muffle furnace for high-temperature sintering at 980℃ for 20h, finally obtaining Li 1.1 Mn 0.6 Co0.3 O2.

[0069] Example 2: A preparation method of a lithium-rich manganese-based positive electrode material, comprising the following steps: Step 1, MnSO4·H2O and FeSO4·6H2O with a molar ratio of 3:1 are dissolved in deionized water to prepare solution A with a concentration of 30 g / L and solution B with a concentration of 70 g / L.

[0070] Step 2, solution A, 15wt% ammonia water, 50g / L CTAB solution and 40g / L sodium hydroxide solution are respectively introduced into a continuous stirred tank reactor, the flow rate of solution A and sodium hydroxide is 30L / h, the flow rate of ammonia water and CTAB solution is 10L / h, the reaction speed is 110Hz, and the reaction is carried out at 40℃ for 5h under the protection of nitrogen atmosphere.

[0071] Step 3, stop introducing solution A and 40g / L sodium hydroxide solution, adjust to introduce solution B and 70g / L sodium hydroxide solution, the flow rate of solution B and sodium hydroxide is 30L / h, ammonia water and CTAB solution continue to be introduced, the flow rate of ammonia water and CTAB solution is 20L / h. Adjust the reaction speed to 260Hz, filter after 2h reaction at 40℃, dry, and the obtained solid particles are Mn 0.75 Fe 0.25 (OH)2precursor.

[0072] Step 4, 0.1mol of Mn 0.75 Fe 0.25 (OH)2is mechanically mixed with 0.154mol of lithium nitrate, and then placed in a muffle furnace for high-temperature sintering at 900℃ for 30h, finally obtaining Li 1.2 Mn 0.6 F e0.2 O2.

[0073] Example 3: A preparation method of a lithium-rich manganese-based positive electrode material, comprising the following steps: Step 1, MnSO4·H2O and ZnSO4·6H2O with a molar ratio of 5:1 are dissolved in deionized water to prepare solution A with a concentration of 50g / L and solution B with a concentration of 100g / L.

[0074] Step 2, solution A, 40wt% ammonia water, 100g / L PVP solution and 60g / L sodium hydroxide solution are respectively introduced into a continuous stirred tank reactor, the flow rate of solution A and sodium hydroxide is 100L / h, the flow rate of ammonia water and PVP solution is 18L / h, the reaction speed is 160Hz, and the reaction is carried out at 40℃ for 2h under the protection of nitrogen atmosphere.

[0075] Step 3, stop feeding solution A and 60 g / L sodium hydroxide solution, adjust to feed solution B and 100 g / L sodium hydroxide solution, the flow rate of solution B and sodium hydroxide is 100 L / h, ammonia and PVP solution continue to feed, the flow rate of ammonia and PVP solution is 36 L / h. Adjust the reaction speed to 250 Hz, filter after 0.5 h reaction at 40℃, dry, and the obtained solid particles are Mn 0.83 Zn 0.17 (OH)2precursor.

[0076] Step 4, take 0.1 mol of Mn 0.83 Zn 0.17 After mechanical mixing of 0.1 mol of Mn 1.3 Mn 0.58 Zn 0.12 O2.

[0077] Figure 1 SEM image of the lithium-rich manganese-based positive electrode material prepared in Example 1 under 6000 times magnification, Figure 2 SEM image of the lithium-rich manganese-based positive electrode material prepared in Example 1 under 5000 times magnification; from Figure 1 and Figure 2 It can be seen that the particles have mixed morphology of sheet and spherical shape, and the spherical particles are filled between the sheet particles, and the degree of close packing is high.

[0078] Figure 3 SEM image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 1, from Figure 3 It can be seen that the particles are sheet-shaped, and there is a certain gap between the stacked sheet particles.

[0079] Figure 4 SEM image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 2, from Figure 4 It can be seen that the particles are basically spherical or spherical, and the particle agglomeration is serious.

[0080] The tap density and the compacted density of the lithium-rich manganese-based positive electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 are tested. When the tap density is tested, the powder is allowed to settle naturally by mechanical vibration; the compacted density is the density of the powder after being compressed under a certain pressure; the test results are shown in Table 1.

[0081] Table 1 Tap density and compacted density of the lithium-rich manganese-based positive electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 As can be seen from Table 1, the tap density and the compacted density of the mixed morphology positive electrode material prepared by the preparation process provided by the application are greater than the tap density and the compacted density of the positive electrode material prepared by Comparative Example 1 and Comparative Example 2, and in combination with Figure 3 and Figure 4 , the inventors propose that the single flaky morphology positive electrode material prepared by Comparative Example 1 is easy to form an overlapping, staggered and aerial structure when stacking, and a large number of wedge-shaped or interlayer voids will remain between the flakes even if vibration or pressure is applied, and the overall porosity is significantly increased, resulting in a lower tap density and a lower compacted density. The spherical or spherical-like morphology positive electrode material prepared by Comparative Example 2 causes uneven particle size distribution and a large size difference due to partial particle agglomeration, which increases the porosity and reduces the filling efficiency and the densification ability of the particles under vibration or pressure, thereby affecting the tap density and the compacted density of the material. The mixed morphology positive electrode material provided by the application has a strong structural continuity in the form of flakes and spherical-like shapes, thereby exhibiting a better tap density and a better compacted density. It can be predicted that the mixed morphology positive electrode material has a more stable conductivity and ion transport performance, and exhibits excellent electrochemical stability.

[0082] The positive electrode materials prepared by Examples 1-3 and Comparative Examples 1-2 are assembled into batteries by the following method: The positive electrode materials prepared by Examples 1-3 and Comparative Examples 1-2 are weighed according to a mass ratio of positive electrode material: conductive graphite: PVDF of 8:1:1, then a proper amount of N-methyl pyrrolidone (NMP) is added for further grinding and stirring to form a uniform slurry. The slurry is uniformly coated on an aluminum foil using a mold, with a coating thickness of 200 μm, and is placed in a drying oven at 90°C for 10 hours, and then cut into a circular piece with a diameter of 12 mm. The circular piece is used as a positive electrode, and a lithium sheet is used as a negative electrode. The electrolyte includes a solvent and LiPF6, wherein the concentration of LiPF6 is 1 mol / L, and the solvent of the electrolyte is a mixed solvent of EC, DEC and DMC in a volume ratio of 1:1:1. The battery is assembled in a glove box according to the order of a snap battery assembly. The performance of the above assembled battery is tested. The assembled battery is left overnight and then placed in a LAND2001CT battery test box for charge and discharge testing under the conditions of 25°C, 1C and a cycle voltage of 2.8-4.8V, and the cycle number is 100 cycles.

[0083] Figure 5 The cycle curve of the battery assembled by the positive electrode materials prepared by Examples 1-3 and Comparative Examples 1-2 is shown in Figure 5 As can be seen, the positive electrode material provided by the application has more excellent cycle performance and chemical stability, and it can be reasonably predicted that the mixed morphology positive electrode material provided by the application in the form of flakes and spherical-like shapes has a longer service life.

[0084] The above-described embodiments are merely preferred specific embodiments of the present application, but the protection scope of the present application is not limited thereto, and any person skilled in the art can make equivalent substitutions or changes within the technical scope of the present application according to the technical solutions and concepts of the present application, which should be covered within the protection scope of the present application.

Claims

1. A lithium-rich manganese-based precursor material, characterized in that, The lithium-rich manganese-based precursor material has the molecular formula Mn. 1-m-n N n (OH)2, wherein N is one or more of Ni, Co, Fe, Al, and Zn, m ranges from 0.1 to 0.4, and n ranges from 0 to 0.4; the lithium-rich manganese-based precursor material has a mixed morphology of plate-like particles and quasi-spherical particles, wherein the plate-like particles are polygonal, and the quasi-spherical particles are distributed among the plate-like particles.

2. The lithium-rich manganese-based precursor material as described in claim 1, characterized in that, The D50 of the spherical particles is 100~500nm.

3. A method for preparing a lithium-rich manganese-based precursor material, characterized in that, Includes the following steps: Step 1: Mix manganese salt, nitrogen metal salt and water to form solution A and solution B. The concentration of metal element in solution A is lower than that in solution B. Step 2, First stage coprecipitation: Solution A, ammonia, additive, and sodium hydroxide solution are introduced into the reaction system respectively, and the reaction is carried out under a protective atmosphere; Step 3, second stage coprecipitation: Stop the flow of solution A, adjust the reaction speed, and introduce solution B, ammonia, sodium hydroxide, and additives into the reaction system, and react under a protective atmosphere; Step 4: Filter and dry. The resulting solid particles are the lithium-rich manganese-based precursor material.

4. The method for preparing the lithium-rich manganese-based precursor material as described in claim 3, characterized in that, The manganese salt is any one or two of manganese nitrate and manganese sulfate; the nitrogen element in the nitrogen metal salt is any one or more of Ni, Co, Fe, Al, and Zn; the nitrogen metal salt is a nitrate or a sulfate; the additive is any one or more of PVP solution, CTAB solution, and SDS solution; in step 1, the molar amounts of manganese in the manganese salt and nitrogen in the nitrogen metal salt are the same as the ratio of Mn to N in the molecular formula of the lithium-rich manganese-based precursor material.

5. The method for preparing the lithium-rich manganese-based precursor material as described in claim 3, characterized in that, In step 2, the reaction speed is 100~200 rpm / min, the reaction time is 2~5 h, and the reaction temperature is 35~55℃; in step 3, the reaction speed is 220~260 rpm / min, the reaction time is 0.5~2 h, and the reaction temperature is 35~55℃.

6. The method for preparing the lithium-rich manganese-based precursor material as described in claim 3, characterized in that, In step 2, the concentration of solution A is 30-50 g / L; the concentration of sodium hydroxide is 40-60 g / L; the concentration of ammonia is 15-40 wt%; the concentration of additive is 50-100 g / L; the flow rate of solution A is 30-100 L / h; the flow rate of sodium hydroxide solution is 30-100 L / h; the flow rate of ammonia is 10-18 L / h; and the flow rate of additive is 10-18 L / h. In step 3, the concentration of solution B is 70~100 g / L; the concentration of sodium hydroxide is 70~100 g / L; the concentration of ammonia is 15~40 wt%; the concentration of additive is 50~100 g / L; the flow rate of solution A is 30~100 L / h; the flow rate of sodium hydroxide solution is 30~100 L / h; the flow rate of ammonia is 20~50 L / h; and the flow rate of additive is 20~40 L / h.

7. A lithium-rich manganese-based cathode material, characterized in that, The molecular formula of the lithium-rich manganese-based cathode material is Li. 1+m Mn 1-m- n N n O2, wherein N is one or more of Ni, Co, Fe, Al, and Zn, m ranges from 0.1 to 0.4, and n ranges from 0 to 0.4; the morphology of the lithium-rich manganese-based cathode material is a mixture of sheet-like particles and quasi-spherical particles, wherein the sheet-like particles are polygonal, and the quasi-spherical particles are distributed among the sheet-like particles.

8. The lithium-rich manganese-based cathode material as described in claim 7, characterized in that, The spherical particles have a D50 of 100~500nm; the lithium-rich manganese-based cathode material has a compaction density of 3.0~3.8g / cm³. 3 The tap density of the lithium-rich manganese-based cathode material is 1.5~2 g / cm³. 3 .

9. A method for preparing a lithium-rich manganese-based cathode material, characterized in that, The precursor material prepared by any one of the lithium-rich manganese-based precursor materials according to claims 1 to 2 or by any one of the preparation methods according to claims 3 to 6 is calcined under an oxygen-containing atmosphere after being mixed with lithium.

10. A battery, characterized in that, This includes the lithium-rich manganese-based cathode material according to any one of claims 7 to 8 or the lithium-rich manganese-based cathode material prepared by the preparation method according to claim 9.

Citation Information

Patent Citations

  • Lithium-enriched manganese-based positive electrode material and preparation method thereof

    CN109686967A

  • Preparation method of full-concentration gradient positive electrode material precursor, full-concentration gradient positive electrode material and preparation method of full-concentration gradient positive electrode material

    CN114291855A

  • Lithium-rich manganese-based precursor and preparation method thereof, lithium-rich manganese-based positive electrode material and lithium ion battery

    CN118047423A

  • Composite modified cobalt-free lithium-rich manganese-based precursor, preparation method thereof and positive electrode material

    CN118894558A

  • Lithium-rich manganese-based positive electrode precursor material, preparation method thereof, positive electrode material and battery

    CN119430323A